2021
DOI: 10.1111/pere.12406
|View full text |Cite
|
Sign up to set email alerts
|

Unaffirmed and color‐blind: Racial worldview and stigma experienced in interracial relationships

Abstract: Marginalization as an interracial couple has been associated with poorer relationship functioning and poorer mental health outcomes. However, what contributes to whether interracial relationship (IR) partners perceive their relationship as stigmatized is not fully understood.Using a racially diverse sample of over 200 participants in IRs, this study addresses group and individual differences in the experience of IR stigma. Results suggest that, despite literature on related constructs such as stigma consciousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Finally, explicitly addressing partners’ understanding of racism can allow for an externalization of it as an institutional phenomenon. By acknowledging institutional racism, partners can forego the associated detriment in relationship quality (Brooks & Morrison, 2021) and engage in critical discussions about how racism affects the family system. As indicated here, interracial relationship partners do discuss individual experiences of discrimination and the topic of police brutality, a sort of color-blind approach, which dismisses experiences of racism, could invite the harming effects of victim blaming into the relationship and add stressors on the relationships from within (Mekawi & Todd, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, explicitly addressing partners’ understanding of racism can allow for an externalization of it as an institutional phenomenon. By acknowledging institutional racism, partners can forego the associated detriment in relationship quality (Brooks & Morrison, 2021) and engage in critical discussions about how racism affects the family system. As indicated here, interracial relationship partners do discuss individual experiences of discrimination and the topic of police brutality, a sort of color-blind approach, which dismisses experiences of racism, could invite the harming effects of victim blaming into the relationship and add stressors on the relationships from within (Mekawi & Todd, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of Research Question 1 offered a direct test of an association between REW and relationship quality, whereas prior studies have theorized about possible connections only indirectly (Brooks, 2022b ). The results concluded that participants' REW is associated with relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this special issue, we will ground the experiences of those in interracial relationships with attention to the race-based power structures that are characteristic of the United States, a western, educated, industrialized, rich, democratic (WEIRD) society. For the purposes of this study, interracial relationships are defined as intimate pairings of individuals in which a person's racial self-identification is different than their partner's (Brooks, 2022b ). Included in this group are mono-racial individuals of different group identifications and relationships in which one or both partners identify as multiracial but there is a difference in racial group heritage between partners (e.g., a person of Black/White racial background in a relationship with a person of Latinx/White background).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations